Link Worker social prescribing to improve health and well-being for people with long-term conditions: qualitative study of service user perceptions. Issue 7 (16th July 2017) - Moffatt, Suzanne; Steer, Mel; Lawson, Sarah; Penn, Linda; O'Brien, Nicola
Abstract : Objectives: To describe the experiences of patients with long-term conditions who are referred to and engage with a Link Worker social prescribing programme and identify the impact of the Link Worker programme on health and well-being. Design: Qualitative study using semistructured interviews with thematic analysis of the data. Intervention: Link Worker social prescribing programme comprising personalised support to identify meaningful health and wellness goals, ongoing support to achieve agreed objectives and linkage into appropriate community services. Setting: Inner-city area in West Newcastle upon Tyne, UK (population n=132 000) ranked 40th most socioeconomically deprived in England, served by 17 general practices. Participants: Thirty adults with long-term conditions, 14 female, 16 male aged 40–74 years, mean age 62 years, 24 white British, 1 white Irish, 5 from black and minority ethnic communities. Results: Most participants experienced multimorbidity combined with mental health problems, low self-confidence and social isolation. All were adversely affected physically, emotionally and socially by their health problems. The intervention engendered feelings of control and self-confidence, reduced social isolation and had a positive impact on health-related behaviours including weight loss, healthier eating and increased physical activity. Management of long-term conditions and mental health in the face of multimorbidity improved and participants reported greater resilience and more effective problem-solving strategies. Conclusions: Findings suggest that tackling complex and long-term health problems requires an extensive holistic approach not possible in routine primary care. This model of social prescribing, which takes into account physical and mental health, and social and economic issues, was successful for patients who engaged with the service. Future research on a larger scale is required to assess when and for whom social prescribing is clinically effective and cost-effective.